2014
DOI: 10.1021/np5001494
|View full text |Cite
|
Sign up to set email alerts
|

NRPS Substrate Promiscuity Leads to More Potent Antitubercular Sansanmycin Analogues

Abstract: Sansanmycins, members of the uridyl peptide antibiotics, are assembled by nonribosomal peptide synthetases (NRPSs), the substrate promiscuity of which results in the diversity of products. Further exploration of the NRPSs' substrate promiscuity by reinvestigating sansanmycin producer strain led to the isolation and structural elucidation of eight new uridyl peptides, sansanmycins H-O (1-8). Among them, sansanmycin L, containing a 6-OH-bicyclic residue and Phe3 first found at the position AA3, exhibited activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…In the case of different species, as reported in the literature, different substituents could be present in the same class of compounds, leading to different NPs including improvements of their biological activities. 34,35 These results are well explained in Figure 4. The BGCs associated to the Chr1 of B. thailandensis species generally encode information for NRPSs to assembly monomers such as alanine-arginine; cysteinethreonine and ornithine-aspartate-serine; while Chr2 assembles cysteine-cysteine, valine-glycine, and malateaspartate most of the time.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…In the case of different species, as reported in the literature, different substituents could be present in the same class of compounds, leading to different NPs including improvements of their biological activities. 34,35 These results are well explained in Figure 4. The BGCs associated to the Chr1 of B. thailandensis species generally encode information for NRPSs to assembly monomers such as alanine-arginine; cysteinethreonine and ornithine-aspartate-serine; while Chr2 assembles cysteine-cysteine, valine-glycine, and malateaspartate most of the time.…”
supporting
confidence: 63%
“…Different chromosomal levels of similarity could imply directly in monomers flexibility leading to improvements in biosynthetic steps ending in different NPs. 34,35 This could be explained observing different clusters related to the production of thailanstatins. Their different levels of similarity are related to thailanstatins-like compounds with different substituents or side chains.…”
mentioning
confidence: 99%
“…1). To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation171819202122232425. A number of synthetic studies have also been reported on uridylpeptide natural products and analogues2627282930313233, some of which have been shown to possess antimicrobial activity78.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, precursor-directed approaches have also been used to leverage the building bock promiscuity of NRPSs. For example, bicyclic amino acids were fed into the sansamycin Streptomyces producing strain, affording a unique analog with a 8-fold lower MIC against M. tuberculosis [145]. Similarly, pacidamycin biosynthetic machinery was sufficiently promiscuous to generate new derivatives in better yields than the natural pacidamycin simply by feeding tryptophan analogues to the producing strain [46].…”
Section: Promiscuity and Engineering Of Pks/nrps Assembly Linesmentioning
confidence: 99%